1990
DOI: 10.1177/096100069002200202
|View full text |Cite
|
Sign up to set email alerts
|

Employment and career surveys: some reflections on their value and relevance

Abstract: A selection of surveys of job destinations, career progression and career patterns of former students of departments of library and information studies m the UK over the past 15 years is reviewed The value and validity of such reviews is questioned Lack of standardization m questions asked and selection of sample populations is noted Developments revealed by the surveys are summarized A decline m the number of students entenng public libraries and threats to the teaching of public librarianship, greater job mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…However, Audunson suggests that although teaching theory during library courses may mean students are less prepared for library work after graduation, in the long term their contribution and understanding may be greater because of their increased theoretical knowledge [17]. This was partially confirmed by Loughridge, who did a follow-up study of Sheffield MA Librarianship graduates and found that many respondents said some theoretical aspects of the course such as management, that seemed to be irrelevant in their first professional posts, later become useful when they moved into more senior roles [24].…”
Section: How Should Librarianship Be Taught?mentioning
confidence: 57%
See 3 more Smart Citations
“…However, Audunson suggests that although teaching theory during library courses may mean students are less prepared for library work after graduation, in the long term their contribution and understanding may be greater because of their increased theoretical knowledge [17]. This was partially confirmed by Loughridge, who did a follow-up study of Sheffield MA Librarianship graduates and found that many respondents said some theoretical aspects of the course such as management, that seemed to be irrelevant in their first professional posts, later become useful when they moved into more senior roles [24].…”
Section: How Should Librarianship Be Taught?mentioning
confidence: 57%
“…One SLQ comment confirms here how perceptions of value may change over time: "my appreciation for some aspects of the course has grown over time -the management modules were deathly dull when I studied them, but have given me some sense of context in which to place my current organisational practices". This reflects Loughridge's finding that some theoretical aspects of library courses such as management, which seemed to be irrelevant in respondents' first professional library posts, later become useful when they moved into more senior roles [24].…”
Section: Fig 5 Relative Importance Of Programme Content Areasmentioning
confidence: 75%
See 2 more Smart Citations
“…A number of studies, such as those of Armstrong [10], Loughridge [11], Loughridge and Sutton [12], Loughridge, Oates and Speight [13], Marcella and Baxter [14], Quarmby, Willett and Wood [15] and Santos, Willett and Wood [16] have examined first destination information and career progression of former students of schools of information and library studies. These are interesting but tend to focus on postgraduate provision and tell us little of the hopes and aspirations of the students or of their reasons for choosing their course of study.…”
mentioning
confidence: 99%